2022
DOI: 10.1002/slct.202104421
|View full text |Cite
|
Sign up to set email alerts
|

Facile and High‐Yielding Synthesis of C(3)‐Aminoisoindolinones Under Metal Catalyst‐Free Conditions

Abstract: C(3)-Aminoisoindolinones have attracted the attention of medicinal chemists due to their unique and stable NÀ CÀ N substructure and possibilities for facile and scalable synthesis of combinatorial libraries. We discovered that para-toluenesulfonic acid (PTSA), an organic protic acid, efficiently catalyzes condensation of isoindolinone-3-ols with primary and secondary amines to furnish C(3) N-substituted isoindolinones in high yields. The NÀ C bond formation reaction is highly efficient and experimentally simpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Rao et al reported the synthesis of a library of 36 new medicinally important C(3)-amino substituted isoindolinone compounds by the reaction of C(3)-hydroxyl isoindolinones with primary or secondary amines in the presence of a catalytic amount of p -TSA (Scheme 72). 117 All the reactions were performed in o -xylene at 120 °C. Authors proposed that in o -xylene, p -TSA has proper p K a and solubility to form acyliminium ion from C(3)-hydroxyl isoindolinones.…”
Section: Synthesis Of Fused-heterocyclic Compoundsmentioning
confidence: 99%
“…Rao et al reported the synthesis of a library of 36 new medicinally important C(3)-amino substituted isoindolinone compounds by the reaction of C(3)-hydroxyl isoindolinones with primary or secondary amines in the presence of a catalytic amount of p -TSA (Scheme 72). 117 All the reactions were performed in o -xylene at 120 °C. Authors proposed that in o -xylene, p -TSA has proper p K a and solubility to form acyliminium ion from C(3)-hydroxyl isoindolinones.…”
Section: Synthesis Of Fused-heterocyclic Compoundsmentioning
confidence: 99%
“…Thus, suitable leaving groups including hydroxyl, [7] alkyl‐/aryloxy, [8] acetoxy, [9] and carbamate [10] were previously used by various groups to generate the active intermediate (NAI). Similarly, varieties of Lewis acids (LAs) including BF 3 ⋅OEt 2 , [11] Sc(OTf) 3 , [12] InCl 3 , [13] AlCl 3 , TiCl 4 , [14] and Sn(NTf 2 ) 4 [15] and Brønsted acids (BAs) including para‐toluene sulphonic acid ( p TsOH) [6e] , and trifluoroacetic acid (TFA) have been utilized for the generation of NAI and studied its subsequent catalytic intra‐ or intermolecular amidoalkylation reactions. Amongst varieties of transition‐metal complexes, the utilization of Au I /Ag I , [16] Sn(NTf) 4 , [15] Ir−Sn, [17] Cu(II), [18] Ni(II), [19] Pd(II), [20] and dicationic Pd(II) for nucleophilic substitution of γ‐hydroxy lactams, Cu(II) and Pd(II) for enantioselective reaction between NAI and nucleophile are noteworthy.…”
Section: Introductionmentioning
confidence: 99%